Measuring Determination of Factors Affecting Firm Value in Agricultural Sector Companies in Indonesia - Yudhistira Ardana; Etty Puji Lestari (JFBA: Journal of Financial and Behavioural Accounting, 2022)
The purpose of this study is to use a panel data model to examine the factors that impact firm value in agriculture sector enterprises in Indonesia. Management initiatives such as earnings management, tax evasion, and debt strategy all influence business value. According to the findings of this study, all variables studied (earnings management, tax evasion, and debt policy) have an impact on business value. All of these variables have a 79.34 percent impact on the company's valuation, with the remaining 20.46 percent impacted by variables outside of the model. Meanwhile, independent studies show that debt and management strategies have little influence and have a negative link with business value. The study's findings may give more information on what elements may be included in measuring business value, which may have implications for investors, particularly those in agriculture sector companies listed on the stock exchange.